Intestinal Rupture Due to a Non-Perforating Foreign Body - Cardoso Gomes, Fabiana; Carvalho Anunciação, John Willer; Brandão Guedes, Paula Elisa; Alberto Carlos, Renata Santiago (Acta Scientiae Veterinariae, 2020)
Background: Intestinal obstruction by a foreign body is a common occurrence in domestic animals, needing the attention of veterinarians and owners, given that a serious complication of this condition is intestinal rupture, with consequent peritonitis. Perforating objects are the ones most often associated with rupture, but any object that obstructs the intestinal tract, if not removed properly, can lead to intestinal rupture, generating a poor prognosis. This article reports a case of intestinal rupture caused by a non-perforating foreign body in a dog. Case: A 1-year-old Chow-Chow dog was taken by its owner to the Portal Pet private clinic, with a history of foreign body ingestion and emesis. The owner reported that he took the animal to veterinary care in another establishment on the day he noticed vomiting, with no other abnormality being detected. An injectable medication was administered, but the owner did not know what it was, and the dog was discharged. After 15 days, the owner sought care at the clinic initially mentioned, due to the persistence of emesis, in addition to the onset of diarrhea and apparent apathy. On physical examination, the dog was apathetic, with pale mucosa and pain on abdominal palpation. A firm structure was felt, located in the epigastric region, compatible with a foreign body. The dog was referred for hospitalization and an abdominal ultrasound was requested, in addition to blood samples for hematological and serum biochemical tests (urea, creatinine, alanine aminotransferase, and alkaline phosphatase). Serology for parvovirus was also performed. The blood count revealed leukopenia (4,800 thousand/mm3) and biochemical analysis showed an increase in alkaline phosphatase (895.5 U/l). The results for parvovirus were negative. Ultrasonography confirmed the presence of a foreign body. The animal was referred for exploratory laparotomy, in which the foreign body was found in the abdominal cavity as a result of intestinal rupture, and peritonitis was observed. The foreign body was removed, the abdominal cavity washed, intestinal raffia made, and an abdominal drain inserted. The foreign body was identified as a silicone makeup sponge. Three days later, the drain was removed. The patient had good post-surgical clinical evolution and was discharged. The prescription given was as follows: omeprazole 1 mg/kg (VO, every 24 h in the morning, for 2 weeks); dipyrone25 mg/kg (VO, TID, for 4 days); cephalexin 25 mg/kg (VO, BID, for 10 days); mineral vitamin supplement based on probiotics and prebiotics 1 tablet/10 kg (VO, every 24 h, for 10 days); vermifuge based on milbemycin oxime and praziquantel 5-25 mg (VO, in a single dose, with repetition after 15 days); enrofloxacin 50 mg 10 mg/kg (VO, every 24 h, for 7 days); immunoglobulinbased on blood plasma, vitamins and minerals 1 tablet/10 kg (VO, BID, until new recommendations); and metronidazole 40 mg/mL oral solution at a dose of 25 mg/kg (VO, BID, for 7 days). As topical treatment, an antiseptic spraybased on laurel, diethylene glycol ether, sodium sulfate, and povidine iodinewas prescribed for surgical wound cleansing, until the suture removal, and the use of a surgical collar was requested. A reassessment was scheduled after 10 days, during which the suture was removed. At this point the dog had fully recovered. Discussion: Intestinal obstruction by a foreign body is a common cause of veterinary emergencies. As observed in the reported case, rupture of the intestinal wall and peritonitis can result. Although the prognosis of the affected animals is guarded, diagnosis prior to the worsening of septicemia as well as immediate surgical intervention were essential for recovery.